DEVELOPMENT OF ENVIRONMENT BASED ANIMATION VIDEO MEDIA AS A STRATEGY FOR DEVELOPING HIGH LEVEL OF THINKING SKILLS KIDS FOR KINDERGARTEN B - Fortina Verawati Sianturi; Anita Yus; Nasriah Nasriah (SENSEI RESEARCH CENTER, 2022)
This study aims to produce learning media in the form of environmental-based animation videos that are valid, feasible and effective used in developing high-order thinking skills of Kindergarten B Immanuel Kids Medan with the help of Powtoon app. This research was conducted at TK B Immanuel Kids Medan. Implementation of this research carried out by in the even semester of the 2021/2022 academic year. The subjects in this study were three expert validators (design experts, media experts, and materials experts), then the teachers and children of Kindergarten B Immanuel Kids Medan. Meanwhile, the object of this research is the development of environmental-based animation media as a strategy for developing children's higher-order thinking skills. The development model that is the reference for this research is the Thiagarajaan development model, namely the 4-D mode l. The data analysis technique used in this research is descriptive analysis technique. Based on the data from the research and discussion that have been described, it can be concluded that the environment-based animated video media was declared valid by the validator, then based on the recapitulation of the practicality of the product, it also stated that the teacher's response to the product developed had 100% practicality as a learning medium. Furthermore, based on the effectiveness assessment obtained from the results of the children's LKPD test, a score of 83.33% was obtained. Therefore, it can be seen that the media requirements are declared APPROPRIATE as learning media in TK B Imamnuel Kids Medan.